Evaluating Supply Chain Transformation of Passenger Vehicle Industry Towards Manufacturing in Bangladesh - Uddin, Md. Rubaiat; Chowdhury, Hasan Maksud; Bin Mamtaz, Al Fattah (ExcelingTech, 2025)
Bangladesh is classified as a lower-middle-income economy by the World Bank, with a Gross National Income (GNI) per capita of 2,824. It is also designated as a Least Developed Country (LDC) by the United Nations, based on low income, human asset deficits, and economic vulnerability. However, in February 2021, the UN Committee for Development Policy (CDP) recommended Bangladesh for LDC graduation, recognizing its progress in income growth, human development, and economic resilience. Bangladesh, which is the second largest economy in South Asia gained independence in 1971. Nearly 54 years have passed, yet customers in the passenger vehicle segment predominantly rely on used, reconditioned cars imported from Japan. These vehicles, allowed for import up to five years after manufacture, continue to dominate the market. However, there is a growing need to shift toward locally manufactured, brand-new vehicles to advance the country's automobile sector. Establishing a domestic automobile manufacturing industry could drive employment, strengthen the local economy, and improve living standards. Thus, many prime points come into limelight like consumer behaviour, government support and infrastructural capability. This study explores the future of the automotive supply chain in Bangladesh, focusing on identifying key factors that could drive its transformation. Utilizing a hypothesis-driven research design, the study analyzes survey responses to uncover consumer preferences and emerging trends shaping the industry. The findings provide critical insights into the potential shift from a reliance on imported reconditioned vehicles to localized manufacturing, highlighting opportunities and challenges within the evolving automotive landscape of Bangladesh.